Islam and healing loss and recovery of an Indo-Muslim medical tradition, 1600-1900 - Alavi, Seema (Palgrave Macmillan, 2008)
Traces the Islamic healing tradition's interaction with Indian society and politics as these evolved in tandem from 1600 to 1900, and demonstrates how an in-house struggle for hegemony can be as potent as external power in defining medical, social and national modernity. A pioneering work on the social and medical history of Indian Islam.